Publishing journal articles - Becker, Lucinda M.; Denicolo, Pam. (Los Angeles, Calif : SAGE, 2012)
Practical, no-nonsense, accessible guide to planning, writing and publishing a journal article.
When, what and where to publish -- Selecting your topic/adapting your work -- Planning and getting started -- Coping with writer's block -- Getting the style right -- Learning how to stop writing your article -- Working with editors and reviewers -- Recovering from rejection -- Intellectual property rights.
Keywords: Academic writing; Academic writing; English language; Technical writing; Authorship